Clinical laboratory strategies for managing pandemic outbreaks - Alotaibi, Maaly Zayed; Alsoor, Seham Sultan; Alnajrani, Amani Sameer; Mobarki, Amjad Ahmed; Albalawi, Afrah Ali; Alsuwaidi, Badriyh Furaih; Alsedmi, Alaa Yehey; Asiri, Mohammed Alhussain (International Journal Of Community Medicine And Public Health, 2024)
This review article comprehensively examines clinical laboratory strategies for managing pandemic outbreaks, with a particular focus on lessons learned from the COVID-19 pandemic. Drawing upon an extensive analysis of existing literature from databases such as PubMed, Web of Science, and Cochrane, as well as manual searches on Google Scholar, the study aims to provide insights into key aspects of pandemic preparedness and response. The literature review encompasses diverse combinations of medical terminology, emphasizing the role and response of clinical laboratories during pandemics. The primary focus areas include rapid test development and deployment, increased testing capacity, sample collection, and transportation protocols, data management, personnel safety, resource allocation, adaptability, and quality control measures. The inclusion of articles in this study adheres to rigorous criteria, ensuring a thorough and robust review process. The findings highlight the critical importance of rapid and accurate diagnostic testing, especially in the early stages of a pandemic, to facilitate timely interventions and containment. Efficient sample collection and transportation systems are crucial for maintaining the integrity of specimens, while advanced data management and reporting systems contribute to informed decision-making. Adaptability and flexibility are identified as indispensable traits for navigating the dynamic challenges of a pandemic, and stringent quality control measures are foundational for upholding the accuracy of diagnostic testing. The review underscores the collaborative efforts needed among clinical laboratories, public health agencies, and research institutions to strengthen global pandemic preparedness and response strategies.